Microbial Growth and Organic Matter Cycling in the Pacific Ocean Along a Latitudinal Transect Between Subarctic and Subantarctic Waters - Giebel, Helge-Ansgar; Arnosti, Carol; Badewien, Thomas H.; Bakenhus, Insa; Balmonte, John Paul; Billerbeck, Sara; Dlugosch, Leon; Henkel, Rohan; Kuerzel, Birgit; Meyerjürgens, Jens; Milke, Felix; Voss, Daniela; et al. (Frontiers in Marine Science, 2021)
The Pacific Ocean constitutes about half of the global oceans and thus microbial processes in this ocean have a large impact on global elemental cycles. Despite several intensely studied regions large areas are still greatly understudied regarding microbial activities, organic matter cycling and biogeography. Refined information about these features is most important to better understand the significance of this ocean for global biogeochemical and elemental cycles. Therefore we investigated a suite of microbial and geochemical variables along a transect from the subantarctic to the subarctic Pacific in the upper 200 m of the water column. The aim was to quantify rates of organic matter processing, identify potential controlling factors and prokaryotic key players. The assessed variables included abundance of heterotrophic prokaryotes and cyanobacteria, heterotrophic prokaryotic production (HPP), turnover rate constants of amino acids, glucose, and acetate, leucine aminopeptidase and β-glucosidase activities, and the composition of the bacterial community by fluorescence in situ hybridization (FISH). The additional quantification of nitrate, dissolved amino acids and carbohydrates, chlorophyll a, particulate organic carbon and nitrogen (POC, PON) provided a rich environmental context. The oligotrophic gyres exhibited the lowest prokaryotic abundances, rates of HPP and substrate turnover. Low nucleic acid prokaryotes dominated in these gyres, whereas in temperate and subpolar regions further north and south, high nucleic acid prokaryotes dominated. Turnover rate constants of glucose and acetate, as well as leucine aminopeptidase activity, increased from (sub)tropical toward the subpolar regions. In contrast, HPP and bulk growth rates were highest near the equatorial upwelling and lowest in the central gyres and subpolar regions. The SAR11 clade, the Roseobacter group and Flavobacteria constituted the majority of the prokaryotic communities. Vertical profiles of the biogeochemical and microbial variables markedly differed among the different regions and showed close covariations of the microbial variables and chlorophyll a, POC and PON. The results show that hydrographic, microbial, and biogeochemical properties exhibited distinct patterns reflecting the biogeographic provinces along the transect. The microbial variables assessed contribute to a better and refined understanding of the scales of microbial organic matter processing in large areas of the epipelagic Pacific beyond its well-studied regions.